Cell Therapy for Nonischemic Dilated Cardiomyopathy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (4th August 2021) - Tripathi, Avnish; Khan, Mohammad Saud; Khan, Abdur Rahman; Vaughn, Vida M.; Bolli, Roberto
Abstract: Cell therapy involves transplantation of human cells to promote repair of diseased or injured tissues and/or cells. Only a limited number of mostly small-scale trials have studied cell therapy in nonischemic cardiomyopathy (NICM). We performed a meta-analysis of randomized clinical trials (RCTs) to assess the safety and efficacy of cell therapy in NICM. Electronic databases were searched for relevant RCTs from inception until August 2020. Outcomes assessed were left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter or volume (LVEDD), quality of life (QoL) indices, and major adverse cardiac events (MACEs). Weighted mean differences (MDs) and standardized mean differences (SMDs) were calculated using random-effects methods. Eleven RCTs with 574 participants were included in the analysis. There was a significant increase in mean LVEF (MD, 4.17%; 95% confidence interval [CI] = 1.66-6.69) and modest decrease in LVEDD (SMD, −0.50; 95% CI = −0.95 to −0.06) in patients treated with cell therapy compared with controls. Cell therapy was also associated with improvement in functional capacity, as assessed by the 6-minute walking distance (MD, 72.49 m; 95% CI = 3.44-141.53). No significant differences were seen in MACEs and QoL indices between treated and control groups. This meta-analysis suggests that cell therapy may improve LV systolic function and may be associated with improvement in LVEDD and functional capacity compared with maximal medical therapy. Cell therapy was safe, with no significant difference in MACEs between treatment and control groups. However, given the limitations of current studies, larger well-designed RCTs are needed to evaluate the efficacy of cell therapy in patients with NICM. : Among 11 studies included in our systematic review, meta-analysis of nine studies that reported mean change in left ventricular systolic function from baseline to the end of follow-up after cell therapy in comparison to control group showed significant increase in left ventricular systolic function over time.